(Drought Vulnerability Study in Gunungkidul Regency, DI Yogyakarta, Indonesia) - Dewi, Luh Wiwin Pradnya; Sulastri, Ni Nyoman; Sulastri, Ngadisih; Sucipta, I Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Gunungkidul, a district in the Special Region of Yogyakarta, is dominated by karst hills and has an average rainfall of 1,881.94 mm/year, making it prone to drought. This study aims to create a drought vulnerability map for the region by scoring and weighting parameters such as rainfall, soil type, land use, slope, and surface temperature. The results show that Gunungkidul has moderate rainfall ranging from 2,100 to 2,385 mm/year, with Mediterranean soils covering 79,254.8 ha (54% of the area), moorland covering 56,229 ha (38%), flat slopes covering 50,037 ha (33.69%), and a homogeneous surface temperature of 26.74°C. The drought hazard index, classified into four classes: safe, somewhat vulnerable, vulnerable, and very vulnerable, indicates that Gunungkidul is generally very vulnerable to geometeorological drought, with rainfall, soil type, and land use being the most influential factors.